The place of the inns in the commercial life of London and western England, 1660-1760 - Chartres, J (1973)
The economic history of England has long been dominated by the Industrial Revolution, examining its degree of uniqueness, and its longer-term implications for both the domestic economy and that of the nations whose advance to the modern industrial state took place rather later. In this study , scholars have tended to concentrate on the period after 1750, often dismissing the previous century rather naively in terms of 'preconditions' for industrial growth. Relatively few have looked at the later seventeenth and early eighteenth centuries in depth, except in the fields of public finance and overseas trade. For most purposes, the century before the Industrial Revolution is still, in Professor Fisher's words, a 'Dark Age'. One sector of the economy, the retail trade and retailing institutions, has been generally deprived of scholarly attention. Apart from the development of the great chain stores in the nineteenth century, the bulk of our knowledge of the sector of the economy stems from research conducted prior to 1920. While age is hardly synonymous with a lack of quality, the time had clearly come for some revision. As scholars such as Professor Eversley have come to stress the significance of changing patterns of consumption in the home market to the Industrial Revolution, this sector of the economy has increasingly demanded more research. [Abstract continued in thesis]